Women in geology. Olga Alekseevna Denisova (1893—1972) - I. A. Starodubtseva; V. V. Romanova (Известия высших учебных заведений: Геология и разведка)
The article presents the biography of O.A. Denisova (1893—1972), one of the first Russian female geologists involved in practical geology. In 1918, she graduated from the Natural Department of the Faculty of Physics and Mathematics of Moscow Higher Women’s Courses. During her studies, she participated in field research in the Moscow Region, on Volkhov and Vychegda rivers under the guidance of A.B. Missuna. In 1923, she graduated from Moscow State University with a degree in geology. Since 1918, O.A. Denisova had worked as a researcher in the Moscow branch of the Geological Committee, since 1920 as a geologist in the Geological Department of the Special Commission for the Study of the Kursk Magnetic Anomaly. Later she was engaged in the study of deposits of building materials and hydrogeological surveys. O.A. Denisova began her activity under the supervision of A.D. Arkhangelsky. The article contains her previously unpublished memories about this famous geologist. O.A. Denisova taught geology and hydrogeology at universities and technical schools in Moscow. In 1936 O.A. Denisova was awarded the degree of Candidate of Geological and Mineralogical Sciences without defending a thesis, and in 1946 the All-Union Certification Commission approved her with the academic rank of Associate Professor at the Department of Geology. O.A. Denisova was awarded the medal “For Valiant Labour during the Great Patriotic War of 1941— 1945” (1946) and “In memory of the 800th anniversary of Moscow” (1948). The collections of rocks and minerals collected by O.A. Denisova during field work in the Kursk and Belgorod regions, are stored in the State Geological Museum named after V.I. Vernadsky of RAS.